Neuromancer - Gibson, William (Gollancz, 2016)
The Matrix unfolds like neon origami beneath clusters and constellations of data. Constructs, AIs, live here. Somewhere, concealed by ice, Neuromancer is evolving. As entropy goes into reverse, Molly's surgical implants broadcast trouble from the ferro-concrete geodesic of the Sprawl. Maelcum, Rastafarian in space, is her best hope of rescue. But she and Case, computer cowboy, are busy stealing data from the almighty Megacorps. If the Megacorps do not get them both, perhaps Case will fall prey to the cheap treachery of Linda Lee, someone as lost as himself.